Enhancing Growth and Yield of Foxtail Millet Using Pearl Oyster Biofouling Fertilizer - Nendissa, Jeanne Ivonne; Riry, Johan; Patty, Jogeneis; Amba, Martha; Wahditiya, Andi Adriani; Lating, Raudatul Janna (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2025)
Hotong (Setaria italica L.), or foxtail millet, is an emerging alternative cereal crop with high adaptability to marginal environments and considerable nutritional value. This study aimed to evaluate the effects of liquid organic fertilizer (LOF) derived from pearl oyster (Pinctada maxima L.) biofouling waste on the growth and yield of hotong cultivated under tropical conditions in Mamala Village, Maluku. A factorial randomized block design was implemented using four fertilizer concentrations (0, 10, 20, and 30 mL·L⁻¹) and two application timings (25 and 50 days after planting, DAP). Results revealed that LOF application significantly enhanced both vegetative and reproductive traits. The concentration of 30 mL·L⁻¹ applied at 25 DAP produced the largest leaf area (64.17 cm²) and highest total biomass (306.91 g), indicating improved nutrient uptake and photosynthetic capacity during early growth. Yield components—including plant height, panicle number, and grain weight—increased by 40–60% relative to the control treatment. These findings demonstrate that organic fertilizer made from aquaculture biofouling waste functions as an effective nutrient source for cereal crops while contributing to environmentally responsible waste management. The integration of aquaculture residues into agricultural fertilizer production aligns with circular economy principles by promoting nutrient recycling, reducing reliance on synthetic fertilizers, and mitigating marine pollution associated with biofouling disposal. The implications of this research highlight the potential for scalable, low-cost, and eco-friendly fertilization strategies that enhance food security in marginal farming areas, strengthen coastal community resilience, and support sustainable linkages between aquaculture and terrestrial crop production systems.